A BRIEF HISTORY OF FINANCIAL SYSTEM AND THE BIRTH OF MONEY - Mhd. Zulkifli Hsb; M.Sabri A.Majid; Yenni Arfah; Marliyah; Rita Handayani; Dalyanto; Disna Anum Siregar (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2022)
In the beginning, human life was very simple. In a sense, for meet their needs, humans simply catch fish, hunt animals or picking fruits that are already in the forest. With increasinghuman population, the longer the needs become more complex in type and the number is getting bigger. So that it is impossible for someone to fulfillhis own necessities of life. Everyone feels the need for products the efforts of others, because human nature as social beings is already a sunnatullah in this world. Therefore, the system of exchange of goods and services is veryneeded to facilitate the process of meeting the needs of life. Developmentthe transaction system continues to evolve to this day. The development begins with barter system, gold and silver money system, paper money system, and probably will continue develop in accordance with the demands of human needs.